Pengaruh Rantai Pasok dan Manajemen Persediaan Terhadap Pengembangan Produk - Yenny Maya Dora; Nugraha Saefudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The intense competition in the business world requires companies to innovate their products so that customers do not switch to competitors' products. Product development is a crucial factor that companies must undertake. This research aims to determine the influence of the supply chain and inventory management on product development. The research method used is quantitative research conducted in pharmaceutical companies. Data were obtained by distributing questionnaires to 60 employees of PT. Pharmacy. The collected data were analyzed using SPSS 26. The research results indicate that the supply chain, together with inventory management, has an impact on product development. This illustrates the crucial role of raw material suppliers and the availability of supporting raw materials in meeting the needs, which will support the success of product development.